Dinero y dinero endógeno: una aproximación post keynesiana y de la circulación - Phitippe-Rocihon, Louis (2002)
The perpose of this paper is to suggest a marriage of Post Keynesian and circuit approaches to credit and money. debt and banks. In this sense, this paper analyses and contrasts the contributions of both theories, which are in fact complementary. The main conclusion is that Post Keynesians and Circuitists have much to learn from one another. The former have not fully incorporated into therr theory the notion of money as bank debt, while the latter lack discussion of banking institutional details, vital for understanding the mechanics of endogeneity. Both approaches need to be further developed. When both approaches have becn properly combined, the a coherent heterodox program may begin.